2020
DOI: 10.1177/0033688220925927
|View full text |Cite
|
Sign up to set email alerts
|

Formative Assessment for Learning How to Learn: Exploring University Student Learning Experiences

Abstract: The push for better English as a Foreign Language (EFL) pedagogy continues in Asia. In Japan, particularly, developing self-regulated learning (SRL) skills is a major objective in the new national curriculum for primary and secondary schools. Research in education suggests the practice of formative assessment (FA) in the classroom fosters SRL skills. The importance of FA in EFL is discussed here, along with an investigation of the relationship between FA and SRL skills of Japanese university students.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The creator can opt to set different backgrounds for the wall. Moreover, Fukuda, Lander, and Pope (2020) state that feedback and instructions can be published by the teachers and students are able to read them or give comments on their friends' posts. Besides, Kharis, Ebner, and Wijayati (2020) illustrate that lecturers can assign tasks to students, write comments, and all students in the classroom can follow the results.…”
Section: Padletmentioning
confidence: 99%
See 1 more Smart Citation
“…The creator can opt to set different backgrounds for the wall. Moreover, Fukuda, Lander, and Pope (2020) state that feedback and instructions can be published by the teachers and students are able to read them or give comments on their friends' posts. Besides, Kharis, Ebner, and Wijayati (2020) illustrate that lecturers can assign tasks to students, write comments, and all students in the classroom can follow the results.…”
Section: Padletmentioning
confidence: 99%
“…When there are enormously educational platforms created to assist the teaching and learning process, Padlet is one of them that is an eminent online board used considerably. This platform supports the learning environment in terms of creating collaborative learning and engaging the students in the lesson (Fukuda et al, 2020;Lestari & Kurniawan, 2018). Although there are aforementioned studies about collaborative writing and the Padlet platform, a combination of both to impact students' writing ability has not been carried out in Vietnam.…”
Section: Research Gap and Conceptual Frameworkmentioning
confidence: 99%
“…An inclusion of scaffolding in self-assessment was also evident in Allal’s (2021) study that formative co-regulation (whole-class discussions on how to produce and revise the target genre) helped enhance fifth- and sixth-graders’ self-regulated learning in first language writing (improved writing quality in drafts and revisions). Despite this positive testimony, Fukuda et al (2022) claimed that students, more often than not, did not have sufficient interactions with peers while developing their self-regulated learning skills. They recommended that co-regulation of learning in technology-assisted learning environments (e.g., e-Portfolios) should play an indispensable role in promoting the uptake of self-regulated learning strategies and self-assessment skills.…”
Section: Recommendations and Implicationsmentioning
confidence: 99%
“…We have some evidence both are in play. Fukuda et al (2020) indicated that student-reported instances of formative assessment in their classes and SRL were inflated, likely due to misunderstandings of the survey questions and/or social response bias. Similarly, Gezer-Templeton et al ( 2017) observed that when "students were asked to identify study strategies they used in a free-response format, rather than selecting study strategies from a checklist, student responses lacked standardization.…”
Section: Limitations Of and Directions For Researchmentioning
confidence: 99%